Corporate performance in 2022 - Matavulj, Noemi (knjige, 2023)
There were several notable factors that affected the performance of Slovenian firms in 2022, among them high inflation, bottlenecks in supply chains, the energy crisis and government price regulation. Overall firms nevertheless improved some of their perfor-mance indicators: they generated higher value-added per employee and increased the ratio of operating revenues to operating expenses, while maintaining indebtedness at one of the lowest levels of the last 20 years.The sectors that were curtailed most by the containment measures were again at the forefront of the improved performance. These include arts, entertainment and recrea-tion, accommodation and food service activities, and also transportation and storage. Amid robust domestic demand, there was also good performance in real estate activi-ties and in construction.By contrast, owing to the energy crisis, government regulation and insufficient domes-tic output, the electricity, gas, steam and air conditioning supply sector recorded loss-es, and performance also worsened in financial and insurance activities.Last year’s improvement in corporate performance was driven primarily by firms focus-ing on the domestic market. But exporters also saw an improvement in certain perfor-mance indicators, despite the huge uncertainty in the international environment.Amid the strong post-pandemic recovery, margins had risen sharply in 2021, allowing firms to compensate for the losses recorded in the previous year, but last year they declined slightly as cost pressures further strengthened, but remained comparable to their average levels between 2016 and 2019.